2019
DOI: 10.1111/aji.13217
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B cells with IL‐35 and IL‐10 expression in a normal and abortion‐prone murine pregnancy model

Abstract: Determination of appropriate immunological interactions between the mother and the fetus and the establishment of immune tolerance are fundamental prerequisites for a successful pregnancy. Among them, the induction of a tolerogenic response to paternal antigens is considered necessary for the success of pregnancy. Disturbed immune tolerance can cause pregnancy disorders, such as spontaneous and recurrent miscarriages or preeclampsia. The crucial work of Aluvihare et al published in 2004 1 indicated for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…It was also demonstrated that IL-10 secreting B cells (B10), but not B effector cells that do not produce IL-10, are prominent in the maintenance of the immune balance during pregnancy [ 43 ]. Furthermore, in our previous work, we have shown that at 14 dpc, abortion-prone mice have an increased proportion of CD19 + CD5 + CD1d high+ cells in the uterine draining lymph nodes when compared to that of mice with healthy pregnancies [ 44 ]. What is more, the frequency of CD19 + CD5 + cells in preeclampsia cases is higher than that of the second and third trimester of healthy pregnancy cases and is correlated with the production of autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…It was also demonstrated that IL-10 secreting B cells (B10), but not B effector cells that do not produce IL-10, are prominent in the maintenance of the immune balance during pregnancy [ 43 ]. Furthermore, in our previous work, we have shown that at 14 dpc, abortion-prone mice have an increased proportion of CD19 + CD5 + CD1d high+ cells in the uterine draining lymph nodes when compared to that of mice with healthy pregnancies [ 44 ]. What is more, the frequency of CD19 + CD5 + cells in preeclampsia cases is higher than that of the second and third trimester of healthy pregnancy cases and is correlated with the production of autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…These cells are increased in the spleen of mice with lupus and are able to suppress Th1 responses and expand Tregs in an IL-35-dependent manner ( 62 ). IL-35 + Bregs have been detected in human decidua ( 361 ), while low frequencies have been found in decidua of abortion-prone mice ( 362 ). IL-35 + B cells have also been detected in intestinal mucosa from patients with Crohn's Disease (CD), but not from ulcerative colitis (UC) ( 363 ).…”
Section: Suppressive Mechanisms Of Bregs By Soluble Moleculesmentioning
confidence: 99%
“…Bregs play a key role in the downregulation of the inflammatory response through an IL-10-dependent mechanism ( 86 ). In addition, compared with normal mice, the percentage of Bregs expressing IL-35 in the peripheral blood of abortive mice is reduced, suggesting the potential involvement of IL-35 in pregnancy maintenance ( 87 ). Can the TGF-β1 released by Bregs also participate in the regulation of the immune balance of the maternal-fetal interface?…”
Section: Tgf-β1 In Fetal-maternal Immune Tolerancementioning
confidence: 99%